Development of evaluation indicators in psychosocial projects: balance between a creative challenge and research rigor - Ajduković, Dean (2008)
Evaluation of psychosocial and community oriented projects includes a series of procedures aiming to determine if project outcomes are achieved by an activity planned to help reach an individually or socially relevant goal. Typically various stakeholders have interest in evaluation of psychosocial projects. These may include project staff and manager, donors, authorities, beneficiaries and community. Sometimes their interest in evaluation seems to be in conflict, but clarification of interests can lead to complementary positions. Evaluation is basically a decision-making tool about the future of a project. The basic assumption in evaluation is that it should identify observable or measurable outcomes (consequences, results) that can be used to demonstrate that the project is reaching the goal and objectives. One of the crucial elements in this process are evaluation indicators which need to satisfy several universal criteria, while their specific content and data collection method should reflect the specifics of a project under evaluation.
Projekt MZOS
ENG